Notes on the Citrus Rust Mite, Phyllocoptruta oleivora (Ashmead), as a Major Pest of Citrus in Indonesia - Retno Dyah Puspitarini; Otto Endarto (AGRIVITA, Journal of Agricultural Science, 2021)
Most citrus farmers in Indonesia believed that rust on citrus fruits resulted from insect attacks. This research aims to determine the cause of rust on citrus fruit and its damage intensity. The study was carried out in commercial citrus plantations in three provinces, on Citrus sinensis and C. reticulata plantations in East Java, C. reticulata and C. suhuensis in West Kalimantan and C. suhuensis in North Sumatra. An additional observation was also conducted to collect mite specimens on citrus plantations in Malang, East Java. Scanning Electron Microscope (SEM) and light microscope were used to observe and identify each collected sample. Results showed that the cause of rust-colored citrus fruit in three provinces is the citrus rust mite, Phyllocoptruta oleivora (Ashmead). It belongs to the family Eriophyidae with two pairs of legs with regular segmentation, five-rayed featherclaws, and a net pattern on prodorsum. The specific damage produced by this mite is rust-colored symptoms. Damage intensity of citrus rust mite in tree provinces averaging 32.6%, ranging from 30 to 40%, and ca. the mite attacks 90% of citrus fruits. Predaceous mites, predaceous insects, and entomo-acaropathogenic fungi are found on plantations.